Versatile synthesis and biological evaluation of novel 3’-fluorinated purine nucleosides - Ren, Hang; An, Haoyun; Hatala, Paul J.; Stevens, William C., Jr; Tao, Jingchao; He, Baicheng (Beilstein Journal of Organic Chemistry, 2015)
A unified synthetic strategy accessing novel 3'-fluorinated purine nucleoside derivatives and their biological evaluation were achieved. Novel 3’-fluorinated analogues were constructed from a common 3’-deoxy-3’-fluororibofuranose intermediate. Employing Suzuki and Stille cross-coupling reactions, fifteen 3’-fluororibose purine nucleosides 1–15 and eight 3’-fluororibose 2-chloro/2-aminopurine nucleosides 16–23 with various substituents at position 6 of the purine ring were efficiently synthesized. Furthermore, 3’-fluorine analogs of natural products nebularine and 6-methylpurine riboside were constructed via our convergent synthetic strategy. Synthesized nucleosides were tested against HT116 (colon cancer) and 143B (osteosarcoma cancer) tumor cell lines. We have demonstrated 3’-fluorine purine nucleoside analogues display potent tumor cell growth inhibition activity at sub- or low micromolar concentration.
Keywords: anticancer; 3’-fluororibonucleoside; purine nucleoside; 6-substituted purine; synthesis